Factors for eliminating plastic in packaging: The European FMCG experts' view. (20th May 2020) - Ma, Xuezi; Park, Curie; Moultrie, James
Abstract: The fast-moving-consumer-goods (FMCG) sector is in the spotlight as a culprit for the current plastic waste problem. However, few studies provide insight into plastic elimination from the FMCG perspective. This qualitative study explores what the FMCG industry encounters when they attempt to address the plastic packaging issue. We conducted 13 semi-structured interviews with selected managers and technology experts in 7 European FMCGs. The analysis uses am original approach, named 'the Factor Mapping Grid', developed to stimulate responses from participants and map relationships between different factors. Results include 7 critical factors, and show that FMCG managers believe that pressure from "consumers" is the most prominent factor in reducing plastic. But, consumers are also equally viewed as a barrier to transition and thus act as a double-edged sword for FMCGs, depending on their awareness of plastic as an issue, and their willingness to take actions. All firms view legislation as an important enabler, but acknowledge that this is out of their control. It is evident that for industry, there is a general desire to reduce plastic, but there is a reluctance to be the first, and thus, a 'we will if you will' phenomenon is observed.